PUSAT BACA “GEROBAK LITERASI “SEBAGAI AKSI NYATA GERAKAN LITERASI SEKOLAH DI SDN KILASAH KECAMATAN KASEMEN - Ulinnuha, Ulinnuha; Hamidah , Hamidah; Khoirunnisa, Sri; Nur Pratama , Rizky; Rahuldi, Rahuldi; Kadafiah, Siti (Jurnal Abdimas Bina Bangsa, 2024)
The Literacy Ranking in Indonesia is a benchmark for the educational progress of the Indonesian nation. Meanwhile, the school literacy movement, which has long been echoed in schools throughout Indonesia, has not been running optimally. This is caused by various factors, one of which is the lack of strategies to maintain a literacy culture and the lack of availability of reading books in schools. So, this community service is carried out to provide contributions related to ideas and initiatives to realize optimal literacy strengthening strategies through literacy carts.  This activity was carried out in three stages, namely the preparation stage including observations at SDN Kilasah, Kilasah sub-district, Kasemen District, coordinating with partners regarding program planning as well as procuring books and designing a reading center in the form of a literacy cart. The second stage of implementation involved bringing a literacy cart to Kilasah Elementary School and providing material and motivation regarding the school literacy movement, reading activities for 15 minutes, then the evaluation stage in the form of reflection, by opening discussions and questions and answers regarding the information and experiences they gained from the reading results. book. The results of the implementation of Community Service went according to expectations, the students at SDN Kilasah showed significant interest in the activities of reading books and processing information as well as practicing the reading content obtained from the Literacy Cart. The PkM team has contributed to strengthening literacy, so it is necessary to provide program assistance so that it is carried out in a sustainable manner, and partners are advised to create more attractive reading centers